EFFECTS OF APPLE AND ORANGE JUICES ON VIABILITY OF REFRIGERATED GOAT SEMEN - ABIOJA, MONSURU OLADIMEJI (Journal of Agricultural Sciences (Belgrade), 2018)
This study investigatedthe effects of apple and orange juiceson viability of refrigerated spermatozoa of West African Dwarf (WAD) goat bucks.Pooled semen samples fromWAD goat bucks were diluted with Tris-egg yolk extenderseachsupplemented with apple and orangejuices at 0, 2.5, 5, 7.5 and 10/100 mL of diluents. The diluted semen samples were assessed for sperm viability and malondialdehyde (MDA) concentrationafter in vitro storage for 240 hours at 5oC. The ability to maintain sperm motility was higher in extenders supplemented with 7.5% orange juice followed by 10% apple juice compared to other treatments (P<0.05). The extenders supplemented with the juices had higher intact acrosome following addition of 2.5%, 5% and 7.5% apple juice, and 5% orange juice compared to other treatments and the control (P<0.05).Orange juice at 10 % had higher percentage membrane integrity compared to other treatments. Consistent reduced (P<0.05) MDAlevels were observed in extenders supplemented with fruit juices and the reduction was more pronounced in extenders supplemented with 10% apple juice compared to other treatments and the control (P<0.05). The findings revealed that addition of the fruit juices to semen extenders were best in10mL/100 mLapple juice and7.5 mL/100 mLorange in their ability to maintain viability of refrigerated spermatozoa.